ANALISIS PENILAIAN HARGA WAJAR SAHAM DAN KEPUTUSAN INVESTASI SECARA FUNDAMENTAL DENGAN MENGGUNAKAN METODE PRICE EARNING RATIO (Studi Keuangan Pada Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI) - Aneu Lutfiana; R. Deni Muhammad Danial; Dicky Jhoansyah (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to determine the fair price of shares and investment decisions fundamentallyby using the Price Earning Ratio approach seen from the development of the company’sfinancial condition. The fundamental variables used are ROE, EPS, DPS, PER, DPR. The typeof research used is quantitative descriptive. This study analyzed six companies as a sample,namely PT Delta Djakarta Tbk, PT Indofood Sukses Makmur Tbk, PT Kalbe Farma Tbk, PTMulti Bintang Indonesia Tbk, PT Jamu and Pharmaceutical Industry Sido Muncul Tbk and PTTempo Scan Pacific Tbk. The sample was obtained using purposive sampling technique. Theresults of this study indicate that PT. Delta Djakarta Tbk is in an overvalued position so thatthe investment decision that can be taken is by selling the shares. While PT Indofood SuksesMakmur Tbk, PT Kalbe Farma Tbk and PT Jamu and Pharmaceutical Industry Sido Muncul Tbkare in a correctly valued position so that the investment decision that can be taken is by holdingthe shares. While PT Multi Bintang Indonesia Tbk and PT. Tempo Scan Pacific Tbk is in anundervalued position so that the investment decision that can be taken is by buying the shares. Keywords: Stock Valuation, Fundamental Analysis, Price Earning Ratio, Intrinsic Value, Investment Decision